Rosmarinic acid suppresses tau phosphorylation and cognitive decline by downregulating the JNK signaling pathway - So Yamamoto (Nature Portfolio, 2021)
Abstract Rosmarinic acid (RA), a polyphenol found in Lamiaceae herbs, is a candidate of preventive ingredients against Alzheimer’s disease (AD) as it potently suppresses the aggregation of amyloid β (Aβ); however, the effect of RA on tau phosphorylation and cognitive dysfunction remains unclear. The present study revealed that RA intake inhibited the pathological hallmarks of AD, including Aβ and phosphorylated tau accumulation, and improved cognitive function in the 3 × Tg-AD mouse model. Additionally, RA intake suppressed hippocampal inflammation and led to the downregulation of the JNK signaling pathway that induces tau phosphorylation. Feeding with RA exerted an anti-inflammatory effect not only in the central nervous system but also in the periphery. Downregulation of the JNK signaling pathway in hippocampus may be a potential mechanism underlying the inhibition of progression of pathology and cognitive deficit by RA feeding.